What the EGM Show’s? Repetitive Non Reentrant VA Synchrony [RNRVAS] - Rajeev Srivastava; Ritesh Sanguri; S. K. Dutta (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Setting in Pacemaker may itself be proarrhythmic occasionally. RNRVAS is one of them which may lead to PMT and Atrial Arrythmias with adverse clinical out come in patients.